Yoga improves functional gait and health-related quality of life for adults with diabetic peripheral neuropathy: a pilot study - Phillips, Chloe E., author; Schmid, Arlene A., advisor; Sample, Pat L., committee member; Tracy, Brian L., committee member (Colorado State University. Libraries, 2015)
Objective: To determine whether health-related quality of life (HRQOL) and functional gait improved after an 8-week yoga intervention among individuals with diabetic peripheral neuropathy (DPN), and whether HRQOL and functional gait were correlated in populations with DPN. Design: An 8-week yoga intervention non-controlled pretest-posttest pilot study. Setting: Colorado State University’s Integrative Rehabilitation Lab Participants: Sample of individuals with DPN (N=15) over the age of 18 recruited from Fort Collins, CO and neighboring towns. Self report balance impairment? Interventions: Each participant took part in an 8-week yoga intervention that met twice per week for one hour each session. Yoga sessions included physical postures, breathing exercises, and meditation. The yoga was modified for persons with DPN and included seated, standing, and exercises laying on the floor. Main outcome measures: The Neuro-QoL was used to assess HRQOL. The Six-Minute Walk Test (6MWT) was conducted to examine walking endurance and the 10-Meter Walk Test was used to evaluate walking speed. Results: HRQOL and functional gait showed fair correlation. HRQOL improved by 8%. Both components of functional gait improved significantly, walking endurance by 15% (p=0.014) and walking speed by 23% (p<0.001). Conclusion: The results demonstrate that yoga is a potential intervention to promote positive improvements in HRQOL and functional gait, including both walking speed and walking endurance, in individuals with DPN. Rehabilitation and medical professionals may consider this as a modality for helping patients manage their DPN.
Keywords: functional gait; neuropathy; yoga; health-related quality of life; diabetes; rehabilitation